The Bolivarian Revolution: Humanism and counterculture - Marín Murillo, Asdrúbal (2020)
The Bolivarian Revolution is a political, economic and ideological process that is located within the movement called socialism of the XXI century. Its revolutionary project is a humanistic, cultural and counter-hegemonic proposal that analyses and confronts the traditional values ​​of an excluding and repressive Venezuela founded on the principles of big capital and excessive accumulation. The Bolivarian Revolution is not just an ideological and political economic approach, at the same time, it is a countercultural, anti-system and humanist movement that seeks a total transformation of the principles and goals of a culture rooted and sustained by the thinking of the traditional groups who belong to the big Venezuelan capital.